Medicine COMPARATIVE STUDY OF WOUND HEALING ACTIVITY OF INDIAN MEDICINAL PLANT AND HERB AGAINST DIABETIC FOOT ULCER (PIPER NIGRUM AND ARACHIS HYPOGAEA) - KUMAR CHANDAN,; SHARMILA KJ, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Diabetic foot ulcers (DFUs) are the most common cause of non-traumatic lower extremity amputations in developing countries. The aim of this pilot study was to evaluate the medicinal plant (fruits) and herbs (seeds) to meet their primary health-care needs healing to DFUs. Methods: Three solvents were used to acquire extracts from powdered parts of the species. The extracts were used for phytochemical screening like a standard procedure. Quantitative assay of antioxidant activity of the extracts using free radical scavenging phenomena such as a 1,1-diphenyl-2- picrylhydrazyl-assay. The antimicrobial activity of the test organisms to the 11 plant extracts was screened using the agar well diffusion method (Perez et al., 1990). Hypotonicity-induced human red blood cell (HRBC) assay performs to determine anti-inflammatory activities. Results: The presence of maximum antioxidant activity found in Arachis hypogaea (ethyl acetate) extract followed by Piper nigrum. The comparative study of these plants and herb species (P. nigrum and A. hypogaea), where P. nigrum, contains more total tannin contents and antioxidant compounds as persistent manner compares to A. hypogaea. Ethanolic and ethyl acetate, extracts of P. nigrum were studied for the in vitro antimicrobial and anti-inflammation against DFU contamination and HRBCs. P. nigrum treated on DFU contamination and HRBC, shown with maximum inhabitation properties for DFU (800 μg/mL). Conclusions: The finding of the present investigation demonstrated that P. nigrum significantly more suppresses the growth of DFU contamination and induces anti-inflammatory activities follow by A. hypogaea.